Development of electrostatic induction coal dust concentration sensor based on plate-ring detection electrode. (1st April 2022) - Chen, Jiange; Li, Dewen; Wang, Kequan; Wang, Jie; Liu, Guoqing; Wu, Fuxiang; Wu, Liang; Hui, Lifeng
Abstract: In order to increase the detection accuracy of coal dust and reduce the maintenance of the coal dust concentration sensor, in this paper, the electrostatic sensor of the plate-ring detection electrode was developed for the detection of coal dust concentration. Through the establishment of the three-dimensional finite element model of the plate-ring detection electrode and the simulation results of COMSOL, the superiority of the plate-ring detection electrode was demonstrated, and the basis for the structure design of the plate-ring detection electrode was provided. The plate-ring detection electrode and the processing circuit of the tiny electrostatic induction signal were designed. Electrostatic induction dust concentration sensor with plate-ring detection electrode was developed. Experiments and data analysis proved that the 1.5-order central moment of the electrostatic induction signal had a high degree of fit with the dust concentration value. The mathematical relationship between the electrostatic induction signal and the dust concentration was determined. The detection error of coal mine dust concentration sensor based on plate-ring detection electrode did not exceed 10%.